Exploring short video apps users’ travel behavior intention: Empirical analysis based on SVA-TAM model - Wang, Cheng; Cui, Wenjing; Zhang, Yating; Shen, Huawen (Frontiers in Psychology, 2022)
Social media had made significant effect on the tourism and hospitality industry. Among diverse types of social media platforms, short video apps (SVA) represented by Tiktok or Douyin had brought great changes to the tourism industry. As new mobile technology platform, short video apps had changed the way for user to obtain travel information, make traveling plans and share the travel experience. Considering the new technology of SVA and the influence in tourism, this research aims to explore the SVA users’ behavior intentions and the adopting of SVA for making travel decision. Therefore, this study extends the technology acceptance model (TAM), including two new variables: electronic word of mouth and electronic trust. An online survey was conducted to short video apps users. PLS-SEM was implemented for data and structural equations analysis of the final obtained 302 samples. In terms of the relationship between variables, this study found that user perceptions of SVA on usefulness and ease of use are powerful predictors of attitudes towards using SVA for travel planning, which maintains consistency with the outcome of previous TAM studies. Additionally, eWOM and eTrust positively influence user attitudes towards using SVA for travel planning even for destination decisions. Therefore, the short video apps should be taken into consideration for tourism marketing and destination branding owes to the effect on the potential users’ behavior intentions.